Impact of gonadotropin-releasing hormone antagonist addition on pregnancy rates in gonadotropin-stimulated intrauterine insemination cycles - Jain, Shikha (J Hum Reprod Sci, 2016)
OBJECTIVES: The objective of the study is to evaluate the efficacy of gonadotropin-releasing hormone (GnRH) antagonist in improving clinical pregnancy rate in gonadotropin-stimulated intrauterine insemination (IUI) cycles in patients of unexplained infertility. STUDY DESIGN: This was a prospective, randomized case-controlled study. SETTINGS: The study was conducted in the infertility clinic of a tertiary care center. MATERIALS AND METHODS: Four hundred twenty-seven women undergoing IUI following controlled ovarian stimulation with gonadotropins (recombinant follicle-stimulating hormone [r-FSH] 75 IU/day) were randomly divided into two groups. Women in Group I received GnRH antagonist (Cetrorelix 0.25 mg/day) in a multiple dose flexible protocol. Women in Group II received r-FSH alone. Ovulatory trigger was given with human chorionic gonadotropin 5000 IU when dominant follicle was ≥18 mm. IUI was performed within 44–48 h. Both groups received similar luteal phase support. Primary outcome measure was clinical pregnancy rate. The trial was powered to detect an absolute increase in clinical pregnancy rate by 13% from an assumed 20% clinical pregnancy rate in the control group, with an alpha error level of 0.05 and a beta error level of 0.20. RESULTS: Clinical pregnancy rate in Groups I and II was 27.6% (n = 56) and 26.5% (n = 54), respectively (P=0.800). Ongoing pregnancy and multiple pregnancy rates were likewise similar between the groups. CONCLUSIONS: Addition of GnRH antagonist to gonadotropin-stimulated IUI cycles results in no significant difference in clinical pregnancy rate.